2009
DOI: 10.5194/amt-2-243-2009
|View full text |Cite
|
Sign up to set email alerts
|

Experimental characterization of the COndensation PArticle counting System for high altitude aircraft-borne application

Abstract: Abstract.A characterization of the ultra-fine aerosol particle counter COPAS (COndensation PArticle counting System) for operation on board the Russian high altitude research aircraft M-55 Geophysika is presented. The COPAS instrument consists of an aerosol inlet and two dual-channel continuous flow Condensation Particle Counters (CPCs) operated with the chlorofluorocarbon FC-43. It operates at pressures between 400 and 50 hPa for aerosol detection in the particle diameter (d p ) range from 6 nm up to 1 µm. Th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
75
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(85 citation statements)
references
References 57 publications
4
75
1
Order By: Relevance
“…The aerosol number concentration of ambient aerosol particles with size diameters between 6 nm and roughly 1 µm was measured using two independent COndensation PArticle counter Systems (COPAS, Weigel et al, 2009), each having two channels. Three of the four channels sample the ambient aerosol with cut-off diameters (in terms of 50% detection efficiency) of 6, 10 and 14 nm, respectively.…”
Section: Instrumentation For Submicron Particle and Trace Gas Measurementioning
confidence: 99%
See 1 more Smart Citation
“…The aerosol number concentration of ambient aerosol particles with size diameters between 6 nm and roughly 1 µm was measured using two independent COndensation PArticle counter Systems (COPAS, Weigel et al, 2009), each having two channels. Three of the four channels sample the ambient aerosol with cut-off diameters (in terms of 50% detection efficiency) of 6, 10 and 14 nm, respectively.…”
Section: Instrumentation For Submicron Particle and Trace Gas Measurementioning
confidence: 99%
“…For the M-55 "Geophysica" this is the COPAS (COndensation PArticle counter System; see Weigel et al, 2009) while an NMASS instrument was operated by the University of Denver on the NASA DC-8 and NASA WB-57F. Similar instruments were implemented on the German DLR Falcon-20 and a balloon borne CPC was utilised by the University of Wyoming.…”
Section: Introductionmentioning
confidence: 99%
“…According to Weigel et al (2009) the inlet efficiency can be compared with the similarly designed and operated inlet system presented by Hermann et al (2001). For submicron particles, the transmission efficiency of the COPAS aerosol inlet is 90 % or higher.…”
Section: Sampling Techniquementioning
confidence: 99%
“…A self-match of the Geophysica aircraft can be excluded. During RECON-CILE one self-match flight was performed (30 January 2010; see Suminska-Ebersoldt et al, 2012) and it was shown that such a self-match becomes directly visible in the data of diverse Geophysica measuring devices like the COPAS system (Weigel et al, 2009). …”
Section: Sootmentioning
confidence: 99%
See 1 more Smart Citation